Research methods in interpreting : a practical resource - Hale, Sandra; Napier, Jemina (New York : Continuum, 2013)
'This is the first book to deliver a comprehensive guide to research methods in all types of interpreting. It brings together the expertise of two world-recognized scholars in spoken and signed language interpreting to cover the full scope of the discipline. It features questions, prompts and exercises throughout to highlight key concepts, provoke thought and encourage reader interaction. It deals fully with research in both conference and community interpreting, offering a variety of perspectives on both. Core areas such as reading and analyzing research literature, practical issues in research and producing research reports are all covered. This book is an indispensable tool for students and researchers of Interpreting as well as professionals and interpreter trainers'--
Includes bibliographical references and index.
Keywords: Translating and interpreting -- Study and teaching; Translating and interpreting -- Research -- Methodology; Translating services; Linguistic models